2018
DOI: 10.1590/0004-282x20170174
|View full text |Cite
|
Sign up to set email alerts
|

Searching for neurological diseases in the Julio-Claudian dynasty of the Roman Empire

Abstract: The gens Julia was one of the oldest families in ancient Rome, whose members reached the highest positions of power. They made history because Julius Caesar, perpetual dictator, great-uncle of the first emperor, Augustus, passed his name on to the Julio-Claudian dynasty with the emperors Tiberius, Caligula, Claudius and Nero. Descriptions of the diseases of these emperors and some of his family members may indicate diagnoses such as epilepsy, dystonia, dementia, encephalitis, neurosyphilis, peripheral neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There are several details in Caligula's biography that support this argument. It has been suggested that members of the Julius family suffered from epilepsy 2,8 . Additionally, several historians point out that, during his childhood, Caligula had episodes of sudden falls in which he lost consciousness and had difficulty remaining upright 3,7,11 .…”
Section: Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…There are several details in Caligula's biography that support this argument. It has been suggested that members of the Julius family suffered from epilepsy 2,8 . Additionally, several historians point out that, during his childhood, Caligula had episodes of sudden falls in which he lost consciousness and had difficulty remaining upright 3,7,11 .…”
Section: Epilepsymentioning
confidence: 99%
“…a "disorder of intellect" and experienced anxiety and insomnia. However, regardless of the nature of the disease, most historians have concluded that Caligula's illness affected his mental health and caused the personality changes that he experienced after his recovery 1,2,3,5,6,7,8,9,10 . After his nearfatal illness, he became an alcoholic, believed he was a deity, and, moreover, he became paranoid about the risk of assassination, which led him to sentence Gemellus and Macro to death 1,2,3,5,6,7,8,9,10,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, official portraits of Roman emperors have been used to support paleopathological diagnoses of neurological diseases among members of the Julio-Claudian dynasty (Camargo 2018). Such investigation has mainly focused on the figures of Gaius (Caligula) and Nero, both described as mentally ill in ancient historiography.…”
Section: A Few Diagnoses Beyond the Veil Of Idealisation Of Julio-claudian Portraiturementioning
confidence: 99%